Use of Pleural Fluid Interferon-gamma Enzyme-linked Immunospot Assay in the Diagnosis of Pleural Tuberculosis - Tika Adilistya; Dalima AW Astrawinata; Ujainah Z Nasir (Acta Medica Indonesiana)
Aim: to evaluate the diagnostic value of an interferon-gamma release assay (IGRA) with enzyme-linked immunospot (ELISPOT) method, T-SPOT.TB, in the diagnosis of pleural TB using pleural fluid mononuclear cells (PFMC). Methods: forty-eight subjects, presumed to have pleural TB with exudative pleural effusion by Light’s criteria, dominated by mononuclear cells, had their pleural fluid specimen tested with T-SPOT.TB, Mycobacterial Growth Indicator Tube (MGIT) culture, and adenosine deaminase (ADA) activity. Other causes of pleural effusion such as heart failure, renal failure, hepatic cirrhosis, and malignancy were excluded. Results: the sensitivity, specificity, positive predictive value, and negative predictive value of the IGRA ELISPOT assay using PFMC for the diagnosis of pleural TB were 100%, 88.89%, 97.5%, and 100%, respectively. Conclusion: IGRA with ELISPOT method performed on PFMC is useful for a rapid and reliable diagnosis of pleural TB in clinical practice, especially in area with high TB burden.